1999
DOI: 10.1111/j.1468-2958.1999.tb00451.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Functions of Talk and Reports of Imagined Interactions (Us) During Engagement and Marriage

Abstract: Research has revealed that individuals v a y in theirphilosophyabout marriage in terms of the amount of sharing and communication that is expected in the relationship. This study examined individual dzperences as a function of gender, marital status (engaged, married) and marital orientation (traditional, independent) on beliefs about talk based on afuncfionai approach and reports of various characteristics of imagined interactions (selftalk). A factor analysis was conducted on beliefs about thefunctions of ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 20 publications
1
29
0
1
Order By: Relevance
“…For instance, as it pertains to frequency and pleasantness, researchers have found that these characteristics of IIs are related to positive relational outcomes (Honeycutt & Wiemann, 1999). Specifically, the authors found that individuals who have positive and frequent imagined interactions are more likely to enjoy serious discussions and are likely to believe that their relationships are more egalitarian than individuals who do not.…”
Section: Imagined Interactionsmentioning
confidence: 95%
See 2 more Smart Citations
“…For instance, as it pertains to frequency and pleasantness, researchers have found that these characteristics of IIs are related to positive relational outcomes (Honeycutt & Wiemann, 1999). Specifically, the authors found that individuals who have positive and frequent imagined interactions are more likely to enjoy serious discussions and are likely to believe that their relationships are more egalitarian than individuals who do not.…”
Section: Imagined Interactionsmentioning
confidence: 95%
“…Imagined interactions have been studied across a variety of relationships including college roommates (Honeycutt & Patterson, 1997), parent=child relationships (Allen, Edwards, Hayhoe, & Leach, 2007), married couples (Honeycutt & Keaton, 2012Honeycutt & Wiemann, 1999), small groups (Turner, Crisp, & Lambert, 2007) and consumer=business relationships (Bolkan & Goodboy, 2011). However, important to our purposes is the fact that IIs play an important role in the college classroom as well.…”
Section: Imagined Interactionsmentioning
confidence: 97%
See 1 more Smart Citation
“…A functional approach answers the question ''why'' rather than ''how'' or ''what'' (Herek, 1987). Such an approach has been utilized to examine talk (Honeycutt & Wiemann, 1999), attributions (Forsyth, 1980), conflict (Coser, 1956;Deutsch, 1973), and attitude change (e.g., Katz, 1960).…”
Section: The Functions Of Interpersonal Argumentmentioning
confidence: 99%
“…Reversely, daily event talk and sharing thoughts and feelings about the relationship are considered as instrumental and functional for the relationship (Canary & Stafford, 1992;Wood, 1993). Evidence for the beneficial effect of this behaviour is obtained in several studies (Buunk & Nijskens, 1980;Canary, Stafford, & Semic, 2002;Honeycutt & Wiemann, 1999;Weigel & Ballard-Reisch, 1999.…”
mentioning
confidence: 99%